Mahkota teleskopik sebagai retainer alternatif gigitiruan lepasan Telescopic crown as alternative retainer of removable denture - Sri W. Rais; Setyawan Bonifacius (Journal of Dentomaxillofacial Science, 2013)
In making removable denture, some aspects must be considered: retention, stabilization, support, comfort, andaesthetic. Retention plays an important role in the success of a removable denture. Retention can be obtained from theundercut area, or friction of the denture’s components to the abutment or abutment. Clasp as a retainer, both of metalcasting and wire have been frequently used in the removable partial denture. The clasp has some shortcomings in itsusing, namely color of the metal can sometimes interfere with the aesthetic of the wearer and cannot be placed on teeththat have experienced extensive caries. Telescopic crown as retainer has several advantages, which can be used oncrown of abutment that has experienced extensive caries or tooth that will be an abutment but have endodontic-treated.On telescopic crowns, retention is obtained from the friction between the primary crowns against secondary crown thatserves as a retainer. This case report describes two cases of a removable denture with a metal framework using atelescopic crown on one tooth that serves as a retainer in the case of one-side free-end edentulous.